Workplace violence towards emergency nurses: A cross-sectional multicenter study. (March 2022) - Alsharari, Abdalkarem F.; Abu-Snieneh, Hana M.; Abuadas, Fuad H.; Elsabagh, Nahed E.; Althobaity, Abdulellah; Alshammari, Farhan F.; Alshmemri, Mohammed S.; Aroury, Ammar M.; Alkhadam, Arab Q.; Alatawi, Suliman S.
Graphical abstract: Abstract: Background: Workplace violence (WPV) against nurses continues to be a challenge within healthcare systems worldwide. Quantifying the burden of WPV in emergency departments will inform the design of appropriate interventions. This study aimed to determine the prevalence, pattern and factors associated with WPV among emergency nurses working in Saudi Arabia. Methods: A multicenter descriptive online survey was conducted using a standardized self-administered questionnaire. Emergency nurses working in public hospitals in the country were invited to participate. Data were analyzed with descriptive statistics and multivariate logistic regression. Results: The study recruited 849 emergency nurses, most (73.7%) had experienced WPV in the past two years; 47.4% experienced physical violence and 94.3% experienced non-physical violence. Most exposures to WPV occurred during the afternoon shifts (70.8%), and mainly perpetrated by family members or relatives of the patients (88.3%). Conclusion: WPV encountered by emergency nurses in Saudi Arabia is alarmingly high, and underreported by the affected nurses. Increased workload, inadequate staffing levels, poorly enforced visitor policy, unmet expectations, and a lack of clarity in reporting were the most frequent causes of WPV. There is a need to reassess the current occupational safety measures in the emergency departments in the country.